2018
DOI: 10.5603/imh.2018.0039
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of injury amongst cruise ship passengers requiring hospitalisation

Abstract: Background: The number of commercial cruise ship passengers continues to rise and is projected to reach 27.2 million passengers worldwide in 2018. Accidental injury aboard these ships can result in serious morbidity and mortality. This study examines the injury mechanisms, patterns, demographics, and outcomes of these injuries which are serious enough to require hospitalisation in order to facilitate administrative, financial, and medical decision making to aid in injury prevention and treatment. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…90 (64%) of the 140 deceased were British. The remainder were other European (16), Asian (22), other nationalities (7) or unspecified nationality (5). The deceased were employed in the deck (39), engine (25) and customer service (86) departments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…90 (64%) of the 140 deceased were British. The remainder were other European (16), Asian (22), other nationalities (7) or unspecified nationality (5). The deceased were employed in the deck (39), engine (25) and customer service (86) departments.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, several studies have reported on mortality in passengers who have sailed in cruise ships and/or other types of passenger vessels [1,2]. Many other studies have reported on morbidity in cruise ship passengers, including injuries [3][4][5], various communicable diseases including gastroenteritis and influenza [3,[6][7][8][9][10], and acute cardiovascular diseases [11]. Little has been reported on mortality and its causes among crew members who serve on board cruise or passenger ships.…”
Section: Introductionmentioning
confidence: 99%
“…8 The locality of Mount Fuji is popular for mountain trekking or hiking, so altitude sickness and lower limb injury are common. By contrast, the most common injury on cruise ship travel has been reported to be lower limb fracture, 9 indicating that injury type reflects the tourist location and typical activities. 1 July and August reflects the main open period of trekking in Mount Fuji, so it was not surprising that access to emergency services increased at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Fatal injuries while traveling are mostly caused by accidents, drowning and homicide, whereas no deadly injuries are often due to traffic accidents, falls and leisure activities [16, 21, 22, 23]. Data on Finnish travelers (leisure and business travelers) with health problems abroad during 2010–2012 supported by another assistance medicine provider could show, that infections were the most common health problem accounting for 60% of all cases, whereas injuries accounted for 14.0% of all calls for service, 17.1% of these injuries were fractures [24].…”
Section: Discussionmentioning
confidence: 99%